An Examination of John Henryism, Trust, and Medication Adherence Among African Americans With Hypertension. (February 2020) - Cuffee, Yendelela L.; Hargraves, Lee; Rosal, Milagros; Briesacher, Becky A.; Allison, Jeroan J.; Hullett, Sandral
Background. John Henryism is defined as a measure of active coping in response to stressful experiences. John Henryism has been linked with health conditions such as diabetes, prostate cancer, and hypertension, but rarely with health behaviors. Aims. We hypothesized that reporting higher scores on the John Henryism Scale may be associated with poorer medication adherence, and trust in providers may mediate this relationship. Method. We tested this hypothesis using data from the TRUST study. The TRUST study included 787 African Americans with hypertension receiving care at a safety-net hospital. Ordinal logistic regression was used to examine the relationship between John Henryism and medication adherence. Results. Within our sample of African Americans with hypertension, lower John Henryism scores was associated with poorer self-reported adherence (low, 20.62; moderate, 19.19; high, 18.12; p < .001). Higher John Henryism scores were associated with lower trust scores (low John Henryism: 40.1; high John Henryism: 37.9; p < .001). In the adjusted model, each 1-point increase in the John Henryism score decreased the odds of being in a better cumulative medication adherence category by a factor of 4% (odds ratio = 0.96, p = .014, 95% confidence interval = 0.93-0.99). Twenty percent of the association between medication adherence and John Henryism was mediated by trust (standard deviation = 0.205, 95% confidence interval = 0.074-0.335). Discussion. This study provides important insights into the complex relationship between psychological responses and health behaviors. It also contributes to the body of literature examining the construct of John Henryism among African Americans with hypertension. Conclusion. The findings of this study support the need for interventions that promote healthful coping strategies and patient–provider trust.